Desain dan Simulasi Gate Otomatis untuk Koridor Rumah Sakit Menggunakan Platform IoT Berbasis ESP8266 untuk Keamanan dan Efisiensi - Danang Purnomo; Indra Fauzi Idris; Muhamad Abdul Aziz; Meinawati Meinawati; Benny Susanto; Nandi Priatna (Jurnal Publikasi Teknik Informatika, 2025)
This study proposes the design and implementation of a smart hospital corridor gate prototype utilizing the ESP8266 microcontroller and Internet of Things (IoT) technology to enhance access control and visitor monitoring. With increasing foot traffic in hospitals, effective access management is crucial to prevent unauthorized entry, ensure safety, and maintain operational efficiency. The proposed system uses the ESP8266 as the main controller, enabling real-time monitoring and data transmission over a wireless network. The system integrates Radio Frequency Identification (RFID) technology to automate the identification process. Visitors are required to carry RFID cards or tags, which are scanned upon entry via an RFID reader installed at the gate. The captured data is then transmitted to a centralized server for real-time monitoring and storage, allowing hospital staff to efficiently track visitor activity. Additionally, to support health screening, the system incorporates a temperature sensor for automatic detection of body temperature and a motion-based servo sensor to detect visitor presence and movement in restricted areas. These sensor readings are also transmitted to the server and displayed through an integrated dashboard interface, providing clear and accessible information to hospital staff. Experimental results demonstrate that the system effectively accelerates visitor data acquisition, enhances surveillance, and supports early detection of health conditions. The integration of IoT and sensor-based automation enables hospitals to implement a more secure and responsive access control mechanism. This prototype holds significant potential for further development in building intelligent healthcare infrastructure and can be adapted for broader applications in environments that require stringent monitoring protocols.